Hubungan Antara Kedisiplinan Belajar Siswa Dengan Prestasi Belajar di SMA Negeri 1 Kota Metro - Hanwar Priyo Handoko (Jurnal Dewantara, 2018)
Discipline is one aspect of education that is very important to note. Without an awareness of the necessity of implementing predetermined rules, teaching is unlikely to achieve maximum targets. This research uses quantitative type which is correlative, and the location of this research is SMA Negeri 1 Kota Metro-Lampung. Based on the data that the authors get is as follows: Student learning discipline is quite high, with a high percentage of 10 people 33.33%, 17 people 56.67% moderate and 3 people 10% low; Student achievement is good enough, with good percentage 17 people 56,66%, 10 people 33,34% enough and 3 people 10% low; and the relationship between Learning Discipline with Learning Achievement has a high level of closeness this is in accordance with the results of data analysis obtained that is the value rxy = 0.790.